Tinjauan Hukum Tentang Urgensi Pengaturan Tata Ruang Desa - FAISAL RIZA, ST A.21207092, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2017)
AbstractDevelopment planning in the village during this time has not touched the aspect to a-space, because it is often the quality of planning development in the village is not based on existing potential. With the presence of Village laws resting basic recognition and subsidiarity as a principle of the new, gives a broader space to the village to do the Setup and management of the potential of its territory for the sake of making the village advanced, prosperous, independent and democratic.Spatial arrangement of the village is basically up to the present there has been no particular settings. Spatial laws which conceptually are top-down is not set up on this subject. Nevertheless some initiatives of the village is constantly evolving to make the policy space of the village, along with the enactment of the legislation. Therefore, the spatial arrangement of urgency is this village became a significant issue as the study of the law that need to be formulated.Keynote : Developmental Planning in Village, Spatial Planning, Spatial Arrangement, Villages LawAbstrakPerencanaan pembangunan di Desa selama ini belum menyentuh aspek ke-ruang-an, karena itu kerapkali kualitas perencanaan pembangunan di desa tidak berbasis pada potensi yang ada. Dengan hadirnya Undang-undang Desa yang disandarkan pada asas rekognisi dan subsidiaritas sebagai prinsip baru , memberikan ruang yang lebih luas kepada desa untuk melakukan penataan dan pengelolaan potensi wilayahnya demi menjadikan Desa Maju, Sejahtera, Mandiri dan Demokratis.Pengaturan Tata Ruang Desa pada dasarnya hingga saat ini belum ada pengaturan khususnya. Undang-undang Penataan Ruang yang secara konseptual bersifat top-down tidak mengatur mengenai hal ini. Meski demikian beberapa inisiatif dari desa terus berkembang untuk membuat produk kebijakan tata ruang desa, seiring dengan diberlakukannya Undang-undang Desa. Karenanya, Urgensi pengaturan tata ruang desa inilah menjadi isu signifikan sebagai kajian hukum yang perlu dirumuskan.Kata Kunci:Kewenangan Desa, Perencanaan Pembangunan Desa, Penataan Ruang, Peraturan Desa, Tata Ruang Desa